Variations in Aggressive and Indolent Behaviour of Central Dentinogenic Ghost Cell Tumor - Radhika Manoj Bavle; Sudhakara Muniswamappa; Soumya Makarla; Reshma Venugopal (Case Reports in Dentistry)
Among the aggressive odontogenic tumors, a few tumors generally ameloblastomas, carry a connotation of being aggressive. But, a rare tumor like central dentinogenic ghost cell tumor (DGCT) can be equally aggressive with a propensity for recurrence. The two cases discussed in this article are divergent in behaviour with features such as presentation, seen in early decades as central intraosseous tumors in the maxilla and mandible. The first case describes an aggressive DGCT, associated with impacted tooth and odontome which showed recurrence into a large solid tumor within a year. The second case arose in accordance with a partially erupted molar which was comparatively innocuous and less aggressive. Both the cases exhibited classic histopathological features. These two unconventional cases of DGCT with a follow-up are being reported here to highlight the variation in behaviour and presentation and also to understand the aggressive nature of the tumor.